Research Of The Temperature Regime Of The Heliopyrolysis Process (Texas Journal of Engineering and Technology, 2025)
The article analyzes the temperature regime in the reactor of the pyrolysis device and the saving of thermal energy consumed for the specific needs of the device, as well as the thermal technical indicators of the device. The article also proposes a heliopyrolysis system with a solar concentrator to provide heat to the pyrolysis reactor. As a result of the use of a solar concentrator in this type of pyrolysis device, it is possible to obtain a temperature of 400-700 ℃. As a result, it allows reducing the specific energy consumption for the pyrolysis process by up to 30%. The objectives of this computational and theoretical research on the heliopyrolysis process are mainly aimed at an approximate assessment of their thermal efficiency, taking into account the degree of optimization of thermal technical parameters